2014
DOI: 10.1177/0894439314547617
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the First-Level Digital Divide in the United States: Gender and Race/Ethnicity Patterns, 2007–2012

Abstract: With the narrowing of Internet access divide, researchers have focused on Internet usage, taking for granted access issues. However, questions remain regarding who has Internet access in the United States: What is the status of the racial divide? Is there still a gender divide? How do Latinos compare to other racial and ethnic minority groups? How does gender intersect with race and ethnicity? I analyze nationally representative data to compare Internet access among adults from 2007 to 2012. I find that women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…As the proportion of United States homes with Internet access grew during the 1990s, and with governmental goals of universal Internet access, numerous reports and studies documented the trends in access across population subgroups. These early reports documented that whites were more likely to have Internet access than other racial groups, and that this divide was a consequence of social factors such as income and educational attainment; studies also consistently showed that men were more likely to access the Internet than women (Campos-Castillo, 2014).…”
Section: Digital Divide: Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the proportion of United States homes with Internet access grew during the 1990s, and with governmental goals of universal Internet access, numerous reports and studies documented the trends in access across population subgroups. These early reports documented that whites were more likely to have Internet access than other racial groups, and that this divide was a consequence of social factors such as income and educational attainment; studies also consistently showed that men were more likely to access the Internet than women (Campos-Castillo, 2014).…”
Section: Digital Divide: Studentsmentioning
confidence: 99%
“…This was, and usually still is, measured along axes of race, gender, geography, and socioeconomic status (Campos-Castillo, 2014;Khalid & Pedersen, 2016). As the proportion of United States homes with Internet access grew during the 1990s, and with governmental goals of universal Internet access, numerous reports and studies documented the trends in access across population subgroups.…”
Section: Digital Divide: Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the specific terminology of digital divide itself, the concept is also constantly evolving. For example, the term was originally centred on the question of having, or not having, access to technologies (Compaine, 2001), what scholars refer to as the first-level digital divide (Campos-Castillo, 2015) or the "digital access divide" (Wei, Teo, Chan, & Tan, 2011). With a global mobile phone internet user penetration exceeding fixed broadband in 2017 (International Telecommunication Union, 2017), the concept of digital divide has evolved to consider the relative inequality between those with more or fewer skills (Hargittai, 2002).…”
Section: The Digital Divide Conceptual Problem Too Many Possible Meanmentioning
confidence: 99%